IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN SCHOOLS - Natalie, Regina Yoantika; Yani, Yuli; Ridwan, Ahmad; Setyantoro, Dwipo; Hikmah, Nurul (Jurnal Ilmiah Global Education, 2023)
The purpose of this study was to determine the level of understanding of schools with blockchain technology. The method used in this research is a literature study approach. Data collection through library research. Based on research data, researchers understand that the application of blockchain-based technology in schools plays a very important role because it makes it easier for teachers to teach, makes it easy for students to understand the material with a simple design, and makes teaching more effective and can control students well. Apart from this, blockchain makes it easy for transactions to pay school finances quickly and all data is recorded neatly without having to record it one by one.